Electro-Peroxone Treatment of Phenol: Process Comparison, the Effect of Operational Parameters and Degradation Mechanism - Turkay, Ozge; Barisci, Sibel; Ozturk, Bahar; Ozturk, Hazal; Dimoglo, Anatoli (Electrochemical Soc Inc, 2017)
The degradation of phenol by novel electro-peroxone (E-peroxone) was investigated in this study. In the first stage of the work, different cathode materials (carbon-PTFE, bronze doped carbon-PTFE and stainless steel) and experimental conditions (i.e. inlet ozone concentration) were evaluated for H2O2 generation. All cathode materials apart from stainless steel generated high amount of H2O2 within 10 min. However, when two carbon-PTFE were used as cathodes, the production rate was faster than the usage of one carbon-PTFE cathode. The production capacity of H2O2 and center dot OH radical in the E-peroxone, ozonation and electrooxidation (EOX) processes were presented comparatively. While high concentration of center dot OH radical was generated in both ozonation and E-peroxone processes from the first min, there was no center dot OH radical production in EOX. While the phenol degradation rate was noticeably low in EOX, E-peroxone process provided complete degradation of phenol. The removal rate was also high in ozonation but it was slower than E-peroxone. Transformation by-products were identified by HPLC. The E-peroxone process leads to the formation of aromatic compounds such as p-benzoquinone, hydroquinone and pyro-catechol, and aliphatic carboxylic acids, mostly oxalic acid and maleic acid. E-peroxone process was found the most cost effective process with 0.0032 kWh g(-1) specific energy consumption. (C) 2017 The Electrochemical Society. All rights reserved.
Keywords: Advanced Oxidation Processes; Waste-Water Treatment; Electrochemical Degradation; Landfill Leachate; Bromate Formation; Drinking-Water; Ozonation; Kinetics; Ozone